Lebanon’s greening imagination - Marroum, Marianne (2013)
This paper examines the narratives of a group of Lebanese authors and artists on nature in Lebanon, collected in an anthology entitled The Lost Space: The Views of Lebanese Authors and Artists on Nature (2009) published by the cultural association of George Yammine, the deceased Lebanese poet media officer and critic of literature and art (1955-2000). The essays of Etel Adnan, Antoine al-Daouihy, Hassan Daoud, Fifi Kallab and Claudia Marchelian, among some others, will form the core of the study. I will deal with their objective description and/or subjective experience and perception of Beirut, nature and the environment in Lebanon as a separate entity, and in its relation to their creative work, whence the symbiosis of the natural, the aesthetic and the creative. I will undertake to analyze in the artists’ discourses the residues of forms and frame of minds of what may be regarded as Mediterranean orientalism, namely the subjective romantic experience of nature, the nostalgia for the green Lebanon of the past, as well as the focus on the beauty of the Lebanese landscape. I hope to show that these elements are paralleled and often dialectically intertwined with a more objective image of a degraded environment, one that is moving towards greater entropy. I will conclude with a sample of variegated reactions and solutions some of the authors put forward: paradoxical expressions of love and pride for this degenerated environment, philosophical arguments that inculcate ecocentric values to public consciousness, and pragmatic solutions that consist of a reconfiguration of landscape in sound ecological manner